Financial sector analysis in the cluster theory context (Georgian case) - Pataraia, Larisa; Geradze, Revaz; Dushuashvili, Tatuli (Technology audit and production reserves, 2017)
The paper assesses the financial services in Georgia in the Cluster Theory context. The aim of the research is to identify the ways of the cluster, the dynamics of its variability, the growth rates as well as the realization of its potential and obstacles for it. The study investigates to identify the unity of the interrelated institutions involved in the financial services as being a necessary condition for the formation of the clusters in the sector. For the purposes of this work, a financial cluster is defined as a unity of sub-clusters, such as commercial banks, microfinance institutions, credit unions, insurance companies, pension funds and the stock market. The efficiency of financial services is estimated on the bases of concentration per location, employment, education accessibility, and the volume of capital investments, GDP growth rate, the average profitability and the rate of innovation. It was determined that there is an incomplete form of financial services trade cluster in Georgia, which highly impacts the country's economy. In order to maintain its sustainable competitiveness, it is important to develop viable policies to promote the organic growth of the cluster.